BO‘LAJAK TARIX O‘QITUVCHILARINI TAYYORLASH JARAYONIGA AKSIOLOGIK YONDASHUVNI JORIY ETISHNING METODIK XUSUSIYATLARI (Scientific journal of the Fergana State University, 2024)
The article presents the theoretical foundations of the axiological position, modern pedagogical technologies and practical methods of its development. It will also highlight ways to improve teachers' skills in interpreting historical events and phenomena from the point of view of values ​​during the lesson. The importance of this technique and its role in forming students' sense of respect for cultural and spiritual values ​​will be shown separately.